2021
DOI: 10.1002/jocc.12173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vicarious Racism Exposure via the Media on College Students of Color: Exploring Affect and Substance Use

Abstract: Given the potential negative effects of vicarious racism, we sought to examine the impact of vicarious racism via the media on college students of color. Using a sample of 217 college students of color, we analyzed positive and negative affect and craving for alcohol and marijuana before and after exposure to media stimuli. Split‐plot analysis of variance results revealed a statistically significant interaction effect between time and group for negative affect, but not cravings for substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similarly, given that college enrollment status was only inquired among young adults ages 18–22 in NSDUH, we could not examine SAM use among older college students. In addition, we could not examine some sociocultural factors unavailable in the NSDUH data but are potentially important to Black/AA and other minoritized student groups, such as racism, immigration status, racial socialization, ethnic identity, cultural values, adverse childhood experiences, and extended family support ( Forster et al, 2018 , Giordano et al, 2021 , Neblett et al, 2010 , Rich and Grey, 2011 , Schwartz et al, 2011 ). Fourth, due to the high heterogeneity of the “other” racial/ethnic group, we were unable to make specific implications for this group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, given that college enrollment status was only inquired among young adults ages 18–22 in NSDUH, we could not examine SAM use among older college students. In addition, we could not examine some sociocultural factors unavailable in the NSDUH data but are potentially important to Black/AA and other minoritized student groups, such as racism, immigration status, racial socialization, ethnic identity, cultural values, adverse childhood experiences, and extended family support ( Forster et al, 2018 , Giordano et al, 2021 , Neblett et al, 2010 , Rich and Grey, 2011 , Schwartz et al, 2011 ). Fourth, due to the high heterogeneity of the “other” racial/ethnic group, we were unable to make specific implications for this group.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous variations to the model, this is a basic moderation that says (1) racial discrimination negatively impacts Black youth adjustment and (2) the strength of this association is weakened under certain conditions. The first part of this model alone has been replicated across various levels and dimensions of racial discrimination, including interpersonal and institutional, peer and teacher, using a range of methodology including survey, daily diary, experimental designs, and public records (Cooper, Burnett, Golden, Butler‐Barnes, & Innis‐Thompson, 2022 ; English et al., 2021 ; Giordano et al., 2021 ; Ortega‐Williams et al., 2022 ), and with multi‐informant reports of youth social‐emotional, psychological, and academic adjustment (Benner et al., 2018 ). Certain moderators have also demonstrated consistent results, such as the benefit of parental cultural socialization (Gibson, Bouldin, Stokes, Lozada, & Hope, 2021 ).…”
Section: Black Lives and Black Research Mattermentioning
confidence: 99%
“…Wofford and colleagues [ 73 ] identified a vicarious effect of sharing discriminatory experiences in interpersonal relationships on mental health. Other research also found associations of direct and vicarious racism with negative affect [ 74 , 75 ], and that vicarious racism occurs from both observation of one’s immediate environment and from media coverage of racist incidents [ 76 ].…”
Section: Introductionmentioning
confidence: 99%